Racial and Ethnic Differences in Sodium Sources and Sodium Reduction Behaviors Among US Adults: NHANES 2017 to 2020 Prepandemic - Jessica Cheng; Anne N. Thorndike; Stella Yi (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Nearly all US adults exceed sodium recommendations, which increases cardiovascular risk. Understanding racial and ethnic differences in sodium sources and behaviors could lead to nuanced public health messaging, dietary interventions, and clinical guidance to achieve population‐level sodium reduction more equitably. Methods and Results Using National Health and Nutrition Examination Survey (NHANES) 2017 to 2020 prepandemic data, racial and ethnic differences in sodium sources and sodium‐related behaviors (eg, salt use at the table and in food preparation, doctor advice to reduce sodium, attempts to reduce sodium, and label reading) were assessed using weighted chi‐square. Given the nutrient database's assumption that rice is salted may be inappropriate for some ethnic groups, we conducted a secondary analysis altering this assumption. Pizza, soup, and chicken were top sources of sodium across racial and ethnic groups. For Asian American adults, 4 top sources were unique (eg, soy‐based condiments). Black adults reported the highest rates of reducing sodium (67% versus 44% among White adults) and receiving physician sodium reduction advice (35% versus 18% among Asian American adults). Asian American adults were the most likely to frequently use salt during food preparation (66% versus Other Race adults 32%) but reported not using salt at the table (39% versus 18% among Mexican American adults). Assuming rice is unsalted reduces Asian American sodium intake estimates by ~325 mg/day. Conclusions To equitably address sodium intake, culturally appropriate advice on sources of sodium and salt usage may be needed, particularly for Asian American adults.